Outcomes following use of VersaWrap nerve protector in treatment of patients with recurrent compressive neuropathies - Hones, Keegan M.; Nichols, David Spencer; Barker, Haley; Cox, Elizabeth; Hones, Jaime A.; Chim, Harvey (Frontiers in Surgery, 2023)
Epineural scarring following previous carpal or cubital tunnel release can lead to pain and permanent dysfunction. To prevent this cascade, nerve wraps are an option. The purpose of this study was to evaluate outcomes following use of VersaWrap nerve protector during surgical decompression and neurolysis in patients with recurrent compressive neuropathies in the upper extremity. Twenty patients comprised the patient cohort, with a mean postoperative follow-up time of 139 days (range: 42-356 days). There were 13 females and 7 males, with a mean age of 43.4 years. Fourteen surgeries were performed for revision cubital tunnel, 5 for revision carpal tunnel, and 1 for revision radial tunnel syndrome. Average duration of symptoms prior to revision surgery with VersaWrap was 2 years (range 9 months to 6 years). Postoperatively, the mean DASH score was 57.7 and VAS 3.1. Mean s2PD median distribution was 7.3, s2PD ulnar distribution 8.9, m2PD median distribution 6.9 and m2PD ulnar distribution 7.3. All patients had subjective improvement of symptoms and were satisfied with their result. No patients in our cohort required further revisional surgery. In conclusion, the use of VersaWrap as a nerve protector following revision surgery for recurrent compressive neuropathies in the upper extremity was safe and effective.